Analisis Penetapan Biaya Pelayanan Perguruan Tinggi - Susanta Susanta (Jurnal Paradigma, 2009)
Specified service price require to be made an audit of to ensure ihat price which have been specified have precisely. Accuracy of pricing can be measured from three domains that is pricing mindset, scope of understanding, and price nanagement. This article comment price audit service of a private university in yogyakarta. Result of Performa import matrix analysis indicate thai from side of scope of undersianding, and management price pricing of service in the university have good, but from session ofpricing minds ci there are two less i/ems that is availability procedure and formula, and also the availability of accurate data. Keyword: price audit, pricing mindset, scope of understanding, dan price inanagemen